NOVEL IMMUNOTHERAPEUTIC TARGETS IN RECURRENT GLIOBLASTOMA AND BRAIN METASTASIS - Maich, William (My University, 2025)
Glioblastoma (GBM) is the common malignant brain tumor in adults, accounting for approximately 15% of all CNS tumors, and 48.6% of malignant brain tumors, with a median survival of approximately 14.6 months and a 5-year survival rate of less than 6.8%. However, despite this dismal prognosis and an aggressive standard of care (SoC) involving maximally safe surgical resection, followed by radiotherapy and chemotherapy with temozolomide (TMZ), minimal clinical progress has been made in the past two decades. GBM is characterized by extensive inter- and intra-tumoral heterogeneity and the presence of therapy-resistance brain tumor initiating cells (BTICs), as well as a highly immunosuppressive tumor microenvironment. Following SoC at primary diagnosis, few therapeutic avenues exist at recurrence disease, owing in part due to a lack of clinically relevant targets, leaving patients to enter clinical trials or palliative care. To this end, I utilized a previously initiated multi-omic target identification pipeline to elucidate potential clinically relevant targets on patient-derived rGBM cells with the with the goal to develop novel therapeutic strategies. We used proteomic and genomic data from primary and recurrent GBM samples to identify potentially suitable tumor associated antigens with a suitable therapeutic window and first identified the tumor necrosis factor (TNF) superfamily ligand, CD70 as being highly expressed at recurrent disease. Genetic perturbation of CD70 expression resulted in a decrease in pro-tumorigenic processes such as proliferation and stem-like cell capacity, as well as increased survival in animal models. We further validated anti-CD70 fragment antigen binding (Fab) regions and produced anti-CD70 CAR Ts, which showed dramatic effect in vitro and in vivo against orthotopic patient-derived xenograft models of GBM. Next, I again utilized our multi-omic pipeline, as well as data from the previous CD70 work, and determined the plasminogen activator, urokinase receptor (PLAUR), or uPAR, as being another target of interest, particularly in rGBM. CRISPR knockout of uPAR significantly disrupts functional characteristics of GBM progression, leading to increased survival in vivo. I further validated the binding efficacy of novel anti-uPAR camelid-derived single-domain antibodies (sdAbs) against rGBM cells in vitro, however these sdAbs alone did not elicit a therapeutic effect. To that end, I developed anti-uPAR CAR Ts which produced potent cytotoxic effects against patient-derived rGBM cells both in vitro and in vivo. Lastly, I demonstrated that anti-uPAR CAR Ts are cytotoxic to macrophages, indicating the potential to target the tumor immune microenvironment. The work presented herein aims to increase the number of viable therapeutic targets available and improve the therapeutic options and clinical outcomes for patients.
Keywords: Glioblastoma;Tumor relapse;CRISPR;Chimeric antigen receptor;Immunotherapy;Patient-derived models;Target identification;Brain metastasis